Lipidic profile among rats submitted to total splenectomy isolated or combined with splenic autotransplant - Simões,Fernanda Correia (2007)
PURPOSE: To evaluate the alterations on plasmatic lipids levels among rats submitted to total splenectomy isolated or combined with splenic autotransplant receiving standard chow during the postoperative period. METHODS: Thirty Wistar rats were divided into three groups: control (C) - sham-operated, total splenectomy - isolated (TS) or combined with splenic autotransplantation (SA). Since the postoperative period, all animals received standard rat chow manipulated in accordance to the American Institute of Nutrition Rodents Diets (1993). The plasmatic levels of total cholesterol (TC), triglycerides (TG), high-density lipoprotein (HDL), low-density lipoprotein (LDL), very-low-density lipoprotein (VLDL), and glucose (GLUC) were analyzed before the surgical procedure and after 6 and 12 weeks. RESULTS: All the animals presented significant increase of TG and VLDL levels. In relation to the other parameters there was no difference among the weeks 0 and 12 in the animals of group C. In TS group significant increase was observed in TC and GLUC levels during the experiment. In SA group TC, HDL, and GLUC levels remained unaffected while HDL levels increased. CONCLUSION: Our findings suggest that isolated total splenectomy alters lipids metabolism in rats fed with standard chow and splenic autotransplantation is effective in restoring its control.